INTEGRATED URBAN REGENERATION: AN EMPIRICAL STUDY OF THE NORMATIVE FRAMEWORK IN SPANISH REGIONS - Amparo Maset-Llaudes; Ana M Fuertes-Eugenio; Pilar Pardo-Forcadell (European Regional Science Association (ERSA), 2011)
The current urban planning model for Spanish cities does not meet the criteria for successful urban sustainability, in fact quite the opposite, it follows the disperse city model introduced twenty years ago by the boom in the construction industry and improved communication infrastructures. In this context, one way for Spanish cities to move towards sustainable principles is to consider integrated urban regeneration (IUR) as an alternative to building new housing. To estimate the impact of IUR on the current model, it is important to know firstly, how it is contemplated in Spanish legislation and applied in urban planning throughout Spain. From the normative point of view, territorial and urban planning decisions are the exclusive competence of the self-governing regions, although the Spanish government is responsible for national land use legislation. This study analyses the applicable urban planning legislation in each region by examining the mandatory regulations (laws and development regulations) on urban and territorial planning, the protection of natural areas, natural resource management, the environment and environmental quality, environmental assessment, housing and laws that explicitly refer to sustainability in each self-governing region, using a series of indicators produced for the purpose based on the contents of the 'White Paper on the Sustainability of Spanish Urban Planning'. This information provides an overview of the situation of IUR at national level and in each self-governing region, verifying the levels of compliance to reveal the gaps in Spanish sustainability legislation. The results of this study are linked to the lines of action in the Leipzig Charter on integrated urban development policy and in particular for deprived urban areas within cities.
Keywords: 330